Determinants of maternal knowledge on neonatal danger signs and care-seeking practices in a rural area of southeastern Ethiopia. Issue 6 (17th December 2021) - Getachew, Tamirat; Assebe Yadeta, Tesfaye; Gereziher, Teklehaimanot; Eyeberu, Addis; Dheresa, Merga
Abstract: Background: Most infants in southeastern Ethiopia are either born at home or discharged from the health facility early and families should be able to recognize signs of newborn illnesses and bring the sick newborn to a health facility to receive care. However, studies are limited and the available studies were conducted in urban areas and/or at an institution level. This study aimed to assess the determinants of maternal knowledge of neonatal danger signs and care-seeking practices. Methods: A community-based cross-sectional study was conducted on 520 post-natal mothers using a multistage sampling method from 1 to 30 March 2019. The data were analysed using SPSS version 20 using binary logistic regression. Statistical significance was declared at p<0.05. Results: Mothers' level of knowledge of neonatal danger signs was 50.2% (95% confidence interval [CI] 46.3 to 54.3) and 61% of them sought healthcare when they noticed danger signs. Maternal education level (adjusted odds ratio [AOR] 2.15 [95% CI 1.11 to 4.17]), husband's education level (AOR 2.05 [95% CI 1.07 to 3.94]), residency (AOR 5.83 [95% CI 2.77 to 12.24]), antenatal visits (AOR 2.10 [95% CI 1.13 to 3.90]), antenatal care (ANC) counselling (AOR 4.33 [95% CI 1.88 to 9.98]) and knowledge about essential newborn care (AOR 3.91 [95% CI 2.05 to 7.48]) were the determining factors. Conclusion: The mothers' level of knowledge of neonatal danger signs was low and unsafe care-seeking practices were identified. The mothers' education level, husbands' education level, residence, ANC visits, counselling during ANC and knowledge about essential newborn care were found to be statistically significant determinants. Most of the mothers take their sick neonates to traditional healers and provide home remedies. Intervention modalities focusing on maternal counselling on the most common symptoms of illness in neonates are essential to increase mothers' recognition of illness and improve care-seeking practices.